Análise funcional dos genes exsF e exsG de Xanthomonas citri subsp. citri - Costa, Maria Lucília Machado da [UNESP] (2015)
The Gram-negative bacterium Xanthomonas citri subsp. citri (Xac) is the causal agent of citrus canker, disease that causes a significant economic impact on the orange production. Molecular studies involving pathosystems like Xac-citrus have been used to as an approach to understand the pathogenic processes. Therewith, the objective of this study was to investigate the expression of exsF and exsG Xac genes and the effect of its silencing in Xac pathogenicity in Rangpur lime (Citrus limonia Osbeck) leaves and also get the proteins coded by them and use it in initial tests of crystallization. The real-time PCR (qRT-PCR) technique was used in the analysis of gene expression.The in planta expression of exsF and exsG genes were evaluated in Xac isolated from Rangpur lime leaves collected at 48, 72 and 120 h after inoculation compared to Xac growing in NA culture. For the production of Xac double mutant having the ExsF and exsG genes silenced, the site-directed mutagenesis technique by PCR using the suicide vector pOK1 was used. For the production of ExsF and ExsG recombinant proteins, the E. coli heterologous expression in the pET SUMO expression vector was used. Finally, the initial crystallization trials were performed using commercial and non-commercial kits. The gene expression analysis showed that the exsF and exsG genes were induced about 10-fold more after 72 hours of Xac infection in Rangpur lime leaves, compared with the Xac grown in the culture medium. The functional assays performed with the Xac Δ3135/3136 double mutant showed that it was avirulent on Rangpur lime leaves, in contrast to the wild type strain Xac 306. Moreover, the mutation reduced the multiplication of the bacteria in planta. The mutation also affected the biofilm production, that was reduced in the mutated strain. Through the heterologous expression assays and protein purification it was possible to obtain only the ExsG protein, soluble and pure enough to be ...